Geographic Information System for Mapping Accommodation Locations in Lhokseumawe City Using the AHP Method and Dijkstra's Algorithm - Wahdana, Aldi; Nurdin; Sujacka Retno (Journal of Applied Informatics and Computing, 2025)
This study aims to develop a web-based Geographic Information System (GIS) to provide recommendations for the best accommodation and the fastest route to the accommodation location in Lhokseumawe City. The Analytical Hierarchy Process (AHP) method is used to determine the priority of accommodation based on five main criteria, namely price, public facilities, cleanliness, security, and year founded. The Dijkstra algorithm is applied to calculate the shortest path from the user's position to the selected accommodation. This study involved 21 accommodations as study objects. The results of the analysis showed that Hotel Diana obtained the highest value of 0.08873, so it was recommended as the main accommodation. The shortest distance from the Faculty of Engineering, Malikussaleh University to Hotel Diana is 11.53857 km. These results indicate that the combination of the AHP method and the Dijkstra algorithm is effective in supporting location-based decision making, as well as making it easier for users to determine appropriate accommodation and the fastest route efficiently.